State Responsibility In Providing Compensation To Victims of Gross Human Rights Violations - Fakhruzy, Agung; Krisnadi Nasution; Ahmad Sholikhin; Frans Simangunsong (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
The philosophical basis for providing compensation lies in the state's responsibility for its failure to prevent crimes. From a juridical perspective, Article 35 of Law Number 26 of 2000 on the Human Rights Court indicates that the provision of compensation is still dependent on a court decision. As such, even when gross human rights violations have occurred and victims are identified, if the accused is not proven guilty in court, they cannot be held accountable for providing compensation to the victims. This situation has the potential to create a vertical normative conflict with Article 28 of the 1945 Constitution, particularly regarding fundamental human rights that must be fulfilled by the state. This study aims to examine the principles and the role of the state in providing compensation to victims of gross human rights violations. It employs a normative legal research method with a conceptual and philosophical approach, and data collection is carried out through literature review and legal document analysis. The research findings show that the principle of state responsibility in providing compensation to victims of gross human rights violations must be grounded in the Universal Declaration of Human Rights (UDHR), the Declaration of Basic Principles of Justice for Victims of Crime and Abuse of Power, and the International Covenant on Civil and Political Rights (ICCPR).